2007
DOI: 10.1158/1055-9965.epi-06-0664
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber and Risk of Colorectal Cancer in the Japan Collaborative Cohort Study

Abstract: To examine the association of dietary fiber with the risk of colorectal cancer in a population with a high incidence of cancer and a low fiber intake, we analyzed the data from the Japan Collaborative Cohort Study. From 1988to 1990 men and women aged 40 to 79 years completed a questionnaire on dietary and other factors. Intake of dietary fiber was estimated using a food frequency questionnaire. Rate ratios (RR) were computed by fitting proportional hazards models. During the mean follow-up of 7.6 years, 443 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
64
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 50 publications
(77 reference statements)
6
64
0
Order By: Relevance
“…Overall, most of the associations in the present study were found for men, which is congruent with two other studies that differentiated between men and women 28,31 ; the remaining cohort studies that performed sex-specific analyses did not find any overall associations. 8,[15][16][17]24,30 The differences seen between men and women are difficult to explain.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, most of the associations in the present study were found for men, which is congruent with two other studies that differentiated between men and women 28,31 ; the remaining cohort studies that performed sex-specific analyses did not find any overall associations. 8,[15][16][17]24,30 The differences seen between men and women are difficult to explain.…”
Section: Discussionsupporting
confidence: 91%
“…25 The present study included more cancer cases from updated registries and had a specific Scandinavian focus with particular emphasis on cereal fiber, especially from high fiber cereal foods. Besides the EPIC study, our results are congruent with four other prospective studies 17,28,30,31 and with a recent nested case-control study, nested within seven UK cohort studies, that found that intake of total dietary fiber was inversely associated with colorectal cancer risk (when using data from food diaries). 26 Only two other studies have found results similar to ours with regard to intake of cereal fiber; 25,30 however, neither attempted to subdivide cereal foods into high-and low fiber cereal foods.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Inverse associations were observed between soluble fibre and insoluble fibre and colon cancer but not rectal cancer. The results of a Japanese collaborative study are consistent with our findings (Wakai et al, 2007). The reasons may be that rectum is empty in most of the time, thus reducing the effect of fibre (McNeil et al, 1981) or because the fermentable rates of fibre and bacterial growth are highest in the colon (Mai et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…(i) In the large bowel, fibre can increase stool bulk, dilute faecal carcinogens, shorten faecal transit time and reduce the contact of carcinogens with the colon epithelium (Bingham, 1990;Schatzkin, 2000). (ii) Fibre can bind to the bile acid, which can produce carcinogens (Wakai et al, 2007). (iii) Fibre can be fermented by gut flora to short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%